Representation of Caste Discrimination and Untouchability in Dulal's Gahugoro Africā (Surkhet Journal, 2023)
This paper presents Dalits as Africans in the poem Gahugoro Africā. Dalits are primarily artisans who engage in various tasks such as crafting temple idols, cobbling shoes, ploughing fields, sweeping the streets, and playing musical instruments like the lyre and tum-tum. They utilize their skills and perform the duties expected of them. However, they get fewer wage and they are hated, humiliated, discriminated, exploited and traumatized in the society by the upper caste people and the nation even in this 21st century. Therefore, the purpose of this paper was to illustrate the presence of caste discrimination and untouchability as depicted by the researcher. The research is significant due to its focus on the inhuman treatment and miserable existence of Dalits in the same society. The exploration of diverse cultures and cultural practices is valuable to academia. The research was conducted using a library-based qualitative approach, utilizing relevant texts and sources to analyze the representation of caste discrimination and untouchability in Dulāl's poem. The researcher has implemented cultural studies perspective and the ideas of Stuart Hall as main and other theorists’ ideas as supporting tools for theoretical parameters. The data were collected by text information, description and record keeping. The researcher finds that as a poet, Dulāl seriously raises question that how Dalits are considered untouchables and distanced them by the so called touchable in Nepali society. Dalits present everywhere so, the speaker strictly demands freedom from every type of shackles of discrimination and untouchability. Freedom from such evil practice is inevitable for Dalits in human civilization. So, it is the representative voice of Dalits in general.